Menakar Keefektifan Mandatory Spending Bidang Pendidikan - Hadiyanto Hadiyanto; Teguh Dwi Prasetyo; Dian Merini; Febrian Yalisman (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2022)
This study aims to map the distribution of education inputs (expenditures) and education outcome indicators, as well as analyze the impact of education expenditure on education outcome indicators in Indonesia. The mapping analysis of expenditure distribution and education outcome indicators was carried out by using biplot analysis. Meanwhile, the impact of education expenditure on outcome indicators was analyzed using panel data regression. The results of the Biplot analysis show that Education Expenditure per Capita has a positive correlation with outcome indicators. In several provinces, the Teacher-Student Ratio (RGM) has a positive correlation with outcome indicators, especially the Gross Enrollment Rate (GER) indicator for SMA level. The results of panel data regression analysis show that School Operational Assistance (BOS), Teacher Allowances, Physical Special Allocation Funds (DAK Fisik) for Education, and Number of Schools have a positive and significant impact on the Net Enrollment Rate (APM) and Compulsory Education and Average Years of Schooling (RLS). This study recommends that the government need to consider education outcome indicators per province in allocating the budget of education expenditure and to ensure the distribution ratios as well as teacher quality to improve the quality of education in each province.